CD8 T-cells from most HIV-infected patients lack ex vivo HIV-suppressive capacity during acute and early infection. - Camille Lécuroux; Isabelle Girault; Antoine Chéret; Pierre Versmisse; Georges Nembot; Laurence Meyer; Christine Rouzioux; Gianfranco Pancino; Alain Venet; Asier Sáez-Cirión; ANRS 147 OPTIPRIM clinical trial (PLoS ONE, 2013)
The strong CD8+ T-cell-mediated HIV-1-suppressive capacity found in a minority of HIV-infected patients in chronic infection is associated with spontaneous control of viremia. However, it is still unclear whether such capacities were also present earlier in the CD8+ T cells from non controller patients and then lost as a consequence of uncontrolled viral replication. We studied 50 patients with primary HIV-1-infection to determine whether strong CD8+ T-cell-mediated HIV suppression is more often observed at that time. Despite high frequencies of polyfunctional HIV-specific CD8+ T-cells and a strong CD4+ T-helper response, CD8+ T-cells from 48 patients lacked strong HIV-suppressive capacities ex vivo. This indicates that the superior HIV-suppressive capacity of CD8+ T-cells from HIV controllers is not a general characteristic of the HIV-specific CD8+ T cell response in primary HIV infection.